2017
DOI: 10.1021/acs.langmuir.7b02378
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Self-Assembling Behavior of 5-Fluorouracil and its N,N′-Dimethyl Derivative: A Spectroscopic and Microscopic Approach

Abstract: Under physiological conditions, 5-fluorouracil (5-FU), an anticancer drug, self-assembles into fibrils by strong hydrogen-bonding network, whereas its N,N'-dimethyl derivative, 5-fluoro-1,3-dimethyluracil (5-FDMU), does not make fibrils due to lack of strong hydrogen-bonding motif. In vitro, 5-FU self-assembly is sensitive to physicochemical conditions like the pH and ionic strength of the solution, which tune the strength of the noncovalent driving forces. Here we report a surprising finding that the buffer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 65 publications
5
41
0
Order By: Relevance
“…Price and co-workers have reported about the tight solvation of 5-FU hydrogen bonding groups by water molecules in pure water . We have also observed no fibril formation of 5-FU in pure water in our previous study . Harmandaries and co-workers also have reported that type of nanostructure tuning of diphenylalanine dipeptide using the higher methanol–water mixture .…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Price and co-workers have reported about the tight solvation of 5-FU hydrogen bonding groups by water molecules in pure water . We have also observed no fibril formation of 5-FU in pure water in our previous study . Harmandaries and co-workers also have reported that type of nanostructure tuning of diphenylalanine dipeptide using the higher methanol–water mixture .…”
Section: Resultssupporting
confidence: 65%
“…Since fluorescence lifetime is insensitive to local signal intensity and fluorophore concentration, FLIM provides significant benefits. , Lifetime images are displayed as a false-color image of the lifetime obtained for each pixel . We have used DCM (4-(dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl)-4H-pyran) (∼6 μM) molecule to probe 5-FU morphologies, as DCM was previously successfully used to detect fibrillar structures. , 5-FU concentration is kept the same for all DMSO–water compositions and it is 38 mM. The high concentration correlates to the recommended physiological and medicinal doses of 5-FU .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations